(untitled) (Journal of Psychiatrists’ Association of Nepal, 2023)
Background: Years of investigation have unveiled numerous connections between cardiovascular diseases (CVDs) and anxiety and depression, and there is even a suggestion that they could mutually contribute to each other. Recent research is starting to reveal a significant occurrence of behavioral risk factors among individuals with anxiety and depression, which could potentially lead to the development of cardiovascular disease. A descriptive cross-sectional study was conducted with the aim of determining the occurrence of psychiatric coexisting conditions among individuals with cardiovascular diseases and identifying the behavioral risk factors among this group Material and Methods: The study took place between May 17, 2022, and January 31, 2023, at Nobel Medical College Teaching Hospital in Biratnagar. To achieve this, a semi-structured questionnaire, which included the Self-Reporting Questionnaire (SRQ-20) developed by the World Health Organization, was employed to screen for psychiatric symptoms in a sample of 200 individuals who were purposefully selected for the study. Results: Out of the 200 patients examined, 160 (which accounts for 80%) were found to be positive on the SRQ screening, with the majority of them being males, totaling 65.62% (n=105). A significant portion of these patients fell within the age range of 19 to 39 years 50% (n=80). The behavioral risk factors include smoking at 76.25%, alcohol abuse at 73.75%, physical inactivity at 60%, and obesity at 70%. The distribution of cardiac conditions in the sample included ischemic heart disease in 54.50% of cases, heart failure in 10.50%, cardiomyopathy in 9.00%, rheumatic heart disease in 11.00%, and post-cardiac intervention in 15.00%. Among those with cardiac diseases, 51.25% were experiencing symptoms of depression, 48.75% had anxiety disorders. Conclusion: There was a notable prevalence of depression and anxiety among patients with cardiovascular diseases.